Infantile-onset inflammatory bowel disease has variable long-term outcomes - Alex Krauthammer; Alex Krauthammer; Ilana Weintraub; Ron Shaoul; Raffi Lev-Tzion; Efrat Broide; Michael Wilschanski; Aaron Lerner; Baruch Yerushalmi; Dror S. Shouval; Hussein Shamaly; Yael Haberman-Ziv; et al. (Frontiers Media S.A., 2023)
Objective and aimInfantile-onset inflammatory bowel disease (IO-IBD), defined as IBD diagnosed at age 2 years or younger, tends to be more severe and refractory to conventional treatment than IBD diagnosed at a later age. However, data about IO-IBD and its long-term follow up are limited. We thus aimed to evaluate the presentation and long-term outcomes of patients with IO-IBD in a retrospective multicenter study.MethodsMedical records of patients diagnosed with IO-IBD in eight medical centers during 2000-2017 with at least 1-year follow up were reviewed. Demographics and disease characteristics at diagnosis including age of onset, disease phenotype and location, surgeries, medical therapy, and comorbid conditions were recorded.ResultsTwenty-three patients with IO-IBD (16 males, 70%) were identified and followed for a median (range) of 51.2 (26.0-110.3) months. The mean ages at presentation and at the last follow up were 14 ± 9.8 and 101 ± 77 months, respectively. Six (26%) patients needed ileostomy already at the time of diagnosis and 20 (87%) were treated with corticosteroids. During long-term follow up, remission was achieved in 16 (73%) patients; of whom, 3 (14%) were without medications and 7 (32%) were in remission with the use of 5-aminosalicylic acid only. One patient needed hemicolectomy and one developed a severe EBV related infection.ConclusionThe majority of patients with IO-IBD achieved long-term remission, despite a severe disease presentation at diagnosis. Surgery rate however is high, mainly during the first months from diagnosis.